Growth, Yield and Quality Responses To Gibberellic acid (GA(3)) of Wax Apple Syzygium samarangense var. Jambu Air Madu Fruits Grown Under Field Conditions - Moneruzzaman, K.M.; Boyce, Amru Nasrulhaq; Osman, Normaniza; Hossain, A.B.M. Sharif (Academic Journals, 2011)
A study was carried out to investigate the effects of gibberellic acid (GA(3)) on the growth and development of the red jambu air madu fruits (Syzygium samarangense). Various horticultural parameters were monitored during two seasons of fruit growth between December, 2008 to December, 2009 with the application of three concentrations of GA(3) at 20, 50 and 100 mg/L. It was observed that the application of GA(3) at 50 mg/L increased fruit length and diameter. Furthermore, it enhanced faster fruit growth and color development in addition to increasing fruit number, weight and yield. It also decreased premature fruit dropping. However, spraying with 20 mg/L GA(3) increased the number of buds and fruit setting and reduced bud dropping before anthesis. With regard to fruit quality, the application of GA(3) at 50 mg/L increased total soluble solids (TSS), total sugar, total biomass and total flavonoids content in the fruits by 112, 97, 45 and 92% compared with the control treatment. In addition, anthocyanin content, total phenol and antioxidant activity was higher in GA(3) treated fruits. From this study, it can be concluded that spraying with 50 mg/L GA(3) once a week results in better yield and quality of jambu madu fruits under field conditions.